1999
DOI: 10.1007/s007870050104
|View full text |Cite
|
Sign up to set email alerts
|

Do inpatients on adolescent units recover? A study of outcome and acceptability of treatment

Abstract: It is possible to investigate outcome in an adolescent unit. The results are encouraging and indicate that this form of treatment can be effective and acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 12 publications
2
21
1
6
Order By: Relevance
“…Balkin and Roland (2007) advocated for utilizing a goal attainment model for adolescents in psychiatric hospitalization, which was effective regardless of differential diagnostic labels. This implication was contrary to the suggestion by Cornsweet (1990) and Jaffa and Stott (1999) that adolescent clients with emotional disorders tend to have more positive outcomes than clients diagnosed with disruptive behavior disorders. The manner in which outcomes were measured, however, in Balkin and Roland's research was quite different.…”
Section: Introductioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Balkin and Roland (2007) advocated for utilizing a goal attainment model for adolescents in psychiatric hospitalization, which was effective regardless of differential diagnostic labels. This implication was contrary to the suggestion by Cornsweet (1990) and Jaffa and Stott (1999) that adolescent clients with emotional disorders tend to have more positive outcomes than clients diagnosed with disruptive behavior disorders. The manner in which outcomes were measured, however, in Balkin and Roland's research was quite different.…”
Section: Introductioncontrasting
confidence: 93%
“…Balkin and Roland (2005) further identified that the goal attainment model was effective in reducing psychiatric symptoms, regardless of client diagnosis. This finding was validated further in this study; Jaffa and Stott's (1999) assertion that clients with emotional disorders have a more positive prognosis than clients with disruptive behavior disorders was addressed as well.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations